PENGARUH CYBER CRIME TERHADAP TINGKAT KEPERCAYAAN MASYARAKAT DALAM BERTRANSAKSI DI BANK SYARIAH KOTA PEKANBARU - Amalia (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2024)
ABSTRACT Many banks have launched digital banking services in the ever-growing digital era to make it easier for their customers to access and carry out transactions. However, hacker attacks can disrupt certain bank digital services. The spread of violations known as cybercrime or internet violations. Some websites steal personal data such as email addresses and modify them by providing unauthorized instructions to programmers to commit cybercrimes. Cybercrime is a significant threat to the banking system, which can affect public trust in Islamic banks. This research aims to analyze the influence of cyber crime on the level of public trust in transactions at sharia banks in the city of Pekanbaru. The research method used is a descriptive quantitative method. With a sample using non-probability sampling with a purposive sampling technique, data was obtained through a questionnaire distributed to the Islamic bank user community in the city of Pekanbaru. The research results show that cyber crime has a significant positive influence on the level of public trust in transactions at Islamic banks. Islamic banks need to improve their security systems and educate the public using Islamic banks regarding steps to prevent cyber crime to increase public trust in Islamic banks. Increasing public confidence in transactions at Islamic banks can be achieved through increasing cyber security and transparency in banking services. Keywords: Cyber ​​Crime, Level of Trust